Has interest towards tales and reading changed throughout the last decade? The literary interest of 6-8-years-old children with special regards to László Nógrády’s and Béla Tóth’s researches - Vass, Dorotea (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Half a decade is a long time. Approximately 50 years ago, Béla Tóth conducted a scientific research related to the role of literature among 6 to 8-year-old children. He was interested in the children’s attitudes towards literature and suggested that research should focus on this age group. Tóth’s theoretical research was supported by empirical research results, which demonstrated that this age group is interested in literary texts. Tóth referred to a previous survey published by László Nógrády in 1917, who also based his research on theoretical foundations concerning the types of literary texts the 6-8-year-old children might prefer. It is a coincidence that 50 years passed between the publications of the two researches, thus in 2017 the 50th anniversary will be celebrated of Tóth’s research, while the 100th of Nógrády’s. However, have pedagogical attitudes towards tales and reading changed throughout all these years? The present study focuses on the Hungarian reform pedagogy while touching upon the Nógrády’s and Tóth’s surveys. The purpose of the study is to reveal certain connections among ideas and thoughts related to tales and reading that were relevant a century ago, 50 years ago and today. I enquire to know whether there are still unsolved research questions as well as innovative obstacles, or common features.